Overexpression of myocardial Gsalpha prevents full expression of catecholamine desensitization despite increased beta-adrenergic receptor kinase. - Vatner, D E (1998)
Inotropic and chronotropic responses to catecholamines in young adult transgenic mice overexpressing myocardial Gsalpha are enhanced. One might predict that over the life of the animal, this chronically enhanced beta-adrenergic receptor stimulation would result in homologous catecholamine desensitization. To test this hypothesis, old transgenic Gsalpha mice and age-matched controls were studied physiologically in terms of responsiveness of left ventricular function (ejection fraction) to isoproterenol in vivo and in vitro in terms of beta-adrenergic receptor signaling. Old transgenic mice still responded to isoproterenol with augmented (P < 0.05) left ventricular ejection fraction (+44+/-3%) compared with age-matched controls (+24+/-1%). Although total beta-adrenergic receptor density was reduced in the old transgenic mice, and G protein receptor kinase 2 (beta-adrenergic receptor kinase) levels were increased, the fraction of receptors binding agonist with high affinity as well as isoproterenol- and G protein-stimulated adenylyl cyclase activities were enhanced. Thus, classical catecholamine desensitization is not effective in attenuation of persistently enhanced responses to sympathetic stimulation in mice overexpressing myocardial Gsalpha. To support this conclusion further, experiments were performed with chronic isoproterenol, which elicited effective desensitization in wild-type controls, but failed to elicit desensitization in overexpressed Gsalpha mice. The results of this study suggest that the lack of protective desensitization mechanisms may be responsible in part for the dilated cardiomyopathy which develops with chronic sympathetic stress over the life of these animals.